TRADISI MASYARAKAT DUSUN PANDAN TERHADAP PEMANFAATAN JENIS-JENIS BAMBU PADA KAWASAN HUTAN DI DESA TIANG TANJUNG KECAMATAN MEMPAWAH HULU KABUPATEN LANDAK - Ibab, Sumiati; Dewantara, Iswan; Siahaan, Sarma (Universitas Tanjungpura, 2016)
This research was motivated by human interaction with the natural environment, especially forests. Where their views on what they want il life can be fulfilled through the views associanted with the environment, thereby forming attitude, custom or traditional. The traditional of utilizing bamboo as handicraft material produces woven products such as Ragak, bubu, nyiru, tengkalang. Pandan Hamlet community lives around the forest area. The forest is a natural resource that provides a lot of benefits to humans ecologically and socially in the form of both timber and non-timber productes, on of which is the bamboo that is very useful in daily life. This research aims to find out the species of bamboo an the local tradition of using species of bamboo that has become a tradition in Pandan Hamlet of Tiang Tanjung Village, Subdistrict of Mempawah Hulu, Landak Regency. Theresults showed that there were five species of bamboo namely, Betung (Dendrocalamus asper, Backer ex Heyne), Munti Bamboo ( Schizostachyum sp) Buluh bamboo (Schizostcyum Zollingeri Stuedel), Abe bamboo (Gigantochloa ballui KM Wong), Yellow bamboo (Bambusa valgaris), of which 2 species for house building materials, two species for handicrafts (derivative product), 1 for traditional cookware and ornamental plants. The traditional related to the use of bamboo species are in the form of hand-made crafts such as ragak, tengkalang, nyiruk, bubu, bakul, penangkin, and offering altar for custom ceremonies, water, pipes, as well as building materials.Keywords: Pandan hamlet community traditional, utilization of bambo.